EFSA cross‐cutting guidance lifecycle. Issue 7 (5th July 2018) - ,; Maurici, Daniela; Garcia Matas, Raquel; Gervelmeyer, Andrea
Abstract : This document describes the lifecycle of cross‐cutting guidance documents in EFSA. Cross‐cutting guidance documents deal with matters of a horizontal nature in fields that affect scientific areas covered by more than one Panel. The main objective of developing cross‐cutting guidance documents is to harmonise food and feed safety risk assessment in EFSA. The document outlines the procedures for the identification of needs for cross‐cutting guidance documents, their development, implementation, their review and revision.